Sustained Yield Forestry in Sweden and Russia: How Does it Correspond to Sustainable Forest Management Policy? - Elbakidze, Marine (Springer Netherlands, 2013)
This paper analyzes how sustained yield (SY) forestry is defined and implemented in Sweden and Russia, two countries with different forest-industrial regimes. We first compare definitions of SY forestry in national legislation and policies. Then we study forest management planning in two large forest management units with respect to: delivered forest products and values, how the harvest level of timber is defined, where the harvest takes place, and what treatments are used to sustain desired forest products and values. In Sweden SY forestry is maximum yield based on high-input forest management, and in Russia it is forestry based on natural regeneration with minimum investments in silviculture. We conclude that how SY forestry contributes to SFM depends on the context. Finally, we discuss the consequences of SY forestry as performed in Sweden and Russia related to its ability to support diverse forest functions, as envisioned in sustainable forest management policy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13280-012-0370-6) contains supplementary material, which is available to authorized users.